Pengaruh Proyek Penguatan Profil Pelajar Pancasila (P5) dalam Penerapan Karakter dan Kreativitas Peserta Didik SMAS Adabiah 2 Padang: Penelitian - Nur Huda; Fitri Arsih; Ganda Hijrah Selaras; Fitri Olvia Rahmi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The shift in curriculum policy in Indonesia towards the Merdeka Curriculum emphasizes the importance of contextual and meaningful learning, one of which is implemented through the Pancasila Student Profile Reinforcement Project (P5). This study aims to evaluate the extent to which the implementation of P5 influences the character and creativity of students at SMAS Adabiah 2 Padang. The method used is descriptive quantitative, with data collected through questionnaires distributed to 10th-grade students. The collected data were analyzed using Microsoft Excel and SPSS. The results show that the P5 project has a significant impact on shaping students' character and enhancing their creativity. The percentage for character and creativity indicators reached 87%, indicating a positive influence. Thus, the P5 initiative has been proven to contribute significantly to the development of student character and creativity at SMAS Adabiah 2 Padang.